Economic impacts of renewable power generation technologies and the role of endogenous technological change - Markus Lutz; Markus Flaute; Ulrike Lehr; Kirsten S. Wiebe (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2015)
This paper brings together the debate on economic impacts of renewable energy (RE) deployment and the discussion on modelling endogenous technological change on the global markets for the different renewable power generation technologies. Economic impacts of RE deployment are still mostly discussed on national level, where different effects have been identified. Recent research for Germany shows positive effects on the macro level and different distributional impacts. High investment in solar photovoltaics (PV) from 2010 to 2012 and induced increases in the RE surcharge are the main drivers. At the same time, cost reductions for wind and solar PV take place on global markets, with global learning curves explaining the cost reductions very well. This calls for better including the international dimension into the modelling. The complex feedback loops between global cost curves and national policies, which react to global learning with some time lags, are not yet integrated into quite complex economic models. These models have to capture different RE technologies, different industries, either delivering the RE technologies or strongly depending on electricity prices, which are influenced by national support policies and macroeconomic development. As a first step to better understand the role of international markets, assumptions on RE exports based on global scenarios can be used. Results show the importance of global markets at least for the German RE industries. If the international dimension is taken into account, mainly positive economic impacts of further RE deployment can be observed.
Keywords: Q28; Q29; C51; 330; renewable energy; global learning curves; policies; economic models